The Endocannabinoid System as a Target in Cancer Diseases: Are We There Yet? - Moreno, Estefanía; Cavic, Milena; Krivokuca, Ana; Casadó, Vicent; Canela, Enric (Frontiers in Pharmacology, 2019)
The endocannabinoid system (ECS) has been placed in the anti-cancer spotlight in the last decade. The immense data load published on its dual role in both tumorigenesis and inhibition of tumor growth and metastatic spread has transformed the cannabinoid receptors CB1 (CB1R) and CB2 (CB2R), and other members of the endocannabinoid-like system, into attractive new targets for the treatment of various cancer subtypes. Although the clinical use of cannabinoids has been extensively documented in the palliative setting, clinical trials on their application as anti-cancer drugs are still ongoing. As drug repurposing is significantly faster and more economical than de novo introduction of a new drug into the clinic, there is hope that the existing pharmacokinetic and safety data on the ECS ligands will contribute to their successful translation into oncological healthcare. CB1R and CB2R are members of a large family of membrane proteins called G protein-coupled receptors (GPCR). GPCRs can form homodimers, heterodimers and higher order oligomers with other GPCRs or non-GPCRs. Currently, several CB1R and CB2R-containing heteromers have been reported and, in cancer cells, CB2R form heteromers with the G protein-coupled chemokine receptor CXCR4, the G protein-coupled receptor 55 (GPR55) and the tyrosine kinase receptor (TKR) human V-Erb-B2 Avian Erythroblastic Leukemia Viral Oncogene Homolog 2 (HER2). These protein complexes possess unique pharmacological and signaling properties, and their modulation might affect the antitumoral activity of the ECS. This review will explore the potential of the endocannabinoid network in the anti-cancer setting as well as the clinical and ethical pitfalls behind it, and will develop on the value of cannabinoid receptor heteromers as potential new targets for anti-cancer therapies and as prognostic biomarkers.